The man-woman and the idiot: Madame de Staël's public/private life - Goodden, A (Oxford University Press, 2007)
Madame de Staël's insistence on talking politics in her daily life as well as in her writing was partly what caused her banishment by Napoleon, and she continued unreformed on return from exile. From living political life at second hand through her father Jacques Necker and her lover Louis de Narbonne both before and during the Revolution, she moved on to promoting its claims in her salon. Yet although she insisted to the Duke of Wellington that she needed politics in order to live, her attitude towards the propriety of female political engagement varied: at times she declare that women should simply be the guardians of domestic space for the opposite sex, at others that denying women access to the public sphere of activism and engagement was an abuse of human rights. This paradox partly explains the persona of the "homme-femme" she presented in society, and it remained unresolved throughout her life. For all the (disappointed) feminist intimations of the Revolution, however, her imaginitve writing, like the Revolution itself, consistently shows woman's attempts at public self-assertion as doomed.